Charged-particle pseudorapidity density at mid-rapidity in p-Pb collisions at √sNN=8.16 TeV - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Deisting, Alexander; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Klewin, Sebastian; Köhler, Markus Konrad; Leardini, Lucia; et al. (The European physical journal. C, Particles and fields, 2019)
The pseudorapidity density of charged particles, dNch/dη, in p–Pb collisions has been measured at a centre-of-mass energy per nucleon–nucleon pair of √sNN=8.16 TeV at mid-pseudorapidity for non-single-diffractive events. The results cover 3.6 units of pseudorapidity, |η|<1.8. The dNch/dη value is 19.1±0.719.1±0.719.1± 0.7 at |η|<0.5. This quantity divided by ⟨Npart⟩ / 2 is 4.73±0.204.73±0.204.73± 0.20, where ⟨Npart⟩ is the average number of participating nucleons, is 9.5% higher than the corresponding value for p–Pb collisions at √sNN=5.02 TeV. Measurements are compared with models based on different mechanisms for particle production. All models agree within uncertainties with data in the Pb-going side, while HIJING overestimates, showing a symmetric behaviour, and EPOS underestimates the p-going side of the dNch/dη distribution. Saturation-based models reproduce the distributions well for η>−1.3. The dNch/dη is also measured for different centrality estimators, based both on the charged-particle multiplicity and on the energy deposited in the Zero-Degree Calorimeters. A study of the implications of the large multiplicity fluctuations due to the small number of participants for systems like p–Pb in the centrality calculation for multiplicity-based estimators is discussed, demonstrating the advantages of determining the centrality with energy deposited near beam rapidity.